LENGTH-WEIGHT RELATIONSHIP, CONDITION FACTOR (k) AND SEX RATIO OF FOUR FISH SPECIES FROM RIVER SILUKO, EDO STATE, NIGERIA - OBOH, I. P; OLOWO , U. C. (Nigerian Journal of Fisheries, 2016)
The length-weight relationship (LWR), condition factor (K) and sex ratio of Ctenopoma kingsleyae, Gnathonemus niger, Gnathonemus petersii and Synodontis schall belonging to three families Anabantidae, Mormyridae, and Mochokidae were studied between March and August, 2015 in River Siluko. The correlation coefficients (r) for Length-weight relationship were highly significant (P ˂ 0.01) and the growth exponent ‘b’ = 2.979, 2.097, 2.793 and 2.813 for C. kingsleyae, G. niger, G. petersii and S. schall respectively, indicate a negative allometric growth pattern. Mean condition factor (K) of 3.594 (C. kingsleyae), 1.652 (G. niger), 1.314 (G. petersii) and 2.723 (S. schall), revealed that all fish species were in good health condition. Except in G. niger (1: 0.59) with significantly higher number of males, a balanced population was observed for the other fish species. Findings from this study will serve as baseline information in River Siluko, and will contribute valuably to the existing data to enhance the management and conservation of these fish species